PROGRAM EDUKASI KESEHATAN REPRODUKSI RAMAH USIA BAGI PRA-REMAJA AWAL - Widyaningrum, Bajeng Nurul; Rani, Destri Maya; Syafira, Mutia (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2026)
This community service programme aims to improve early adolescents' knowledge of reproductive health through age-appropriate education. The activity was carried out on 20 children aged 10–12 years who are members of PMR Mula at PMI Semarang City using a one group pre-test–post-test design. Education was provided through interactive lectures, discussions, educational games, and visual media. The results showed a significant increase in participants' understanding of physical changes, psychological changes, and personal hygiene during puberty. The average increase in knowledge reached more than 30%. These findings indicate that an age-appropriate educational approach is effective in improving reproductive health literacy and helping children prepare for puberty in a healthy and safe manner.